2017
DOI: 10.1007/s11695-017-2842-z
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Effects of the Adjustable Gastric Band on Esophageal Motility in Patients Who Present for Band Removal

Abstract: Patients with a history of LABG can have esophageal dysmotility whether they are symptomatic or asymptomatic. Based on existing literature, we recommend pre-operative manometry in these patients requesting revisional surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…New-onset reflux symptoms after sleeve gastrectomy could be due to several pathophysiological changes, including increased intragastric pressure, esophageal dysmotility, decreased lower esophageal sphincter pressure and delayed gastric emptying [ 33 37 ]. While changes to esophageal motility after GB could have predisposed RLSG patients to increased risks of reflux symptoms [ 38 ], efforts were made to prevent these patients from undergoing RLSG in this surgical practice.…”
Section: Discussionmentioning
confidence: 99%
“…New-onset reflux symptoms after sleeve gastrectomy could be due to several pathophysiological changes, including increased intragastric pressure, esophageal dysmotility, decreased lower esophageal sphincter pressure and delayed gastric emptying [ 33 37 ]. While changes to esophageal motility after GB could have predisposed RLSG patients to increased risks of reflux symptoms [ 38 ], efforts were made to prevent these patients from undergoing RLSG in this surgical practice.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the question as to whether all patients who have failed LAGB should undergo HRM in addition to standard studies like EGD prior to revisional surgery. Tchokouani et al [27] recently reported on the preoperative HRM results of 25 patients with LAGB failures requiring revisional surgery; 72% of patients had intact bands at the time of HRM, and all patients with food intolerance had their bands deflated prior to HRM. The threshold for normal esophageal motility was set at > 70% peristalsis based on the Chicago classification system [27].…”
Section: Discussionmentioning
confidence: 99%
“…Tchokouani et al [27] recently reported on the preoperative HRM results of 25 patients with LAGB failures requiring revisional surgery; 72% of patients had intact bands at the time of HRM, and all patients with food intolerance had their bands deflated prior to HRM. The threshold for normal esophageal motility was set at > 70% peristalsis based on the Chicago classification system [27]. Overall, 40% of patients were found to have esophageal dysmotility irrespective of the presence of obstructive symptoms; the authors recommended routine preoperative HRM for the management of all LAGB failures.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of increased intrabolus pressure on HRM have also been shown to correlate with the presence of dysphagia and regurgitation symptoms in LAGB patients [24]. However, patients with esophageal dysmotility after LAGB are often asymptomatic, and there has been no correlation found between the presence of symptoms and esophageal dysmotility [25]. Thus, the clinician's threshold to obtain HRM should be low in patients with a prior history of LAGB.…”
Section: Laparoscopic Adjustable Gastric Banding and Esophageal Motilitymentioning
confidence: 99%